Complement System Inhibition Modulates the Pro-Inflammatory Effects of a Snake Venom Metalloproteinase - Luchini, Lygia Samartin Gonçalves; Pidde, Giselle; Squaiella-Baptistão, Carla Cristina; Tambourgi, Denise V. (Frontiers in Immunology, 2019)
Envenomation by Bothrops snakes causes prominent local effects, including pain, oedema, local bleeding, blistering and necrosis, and systemic manifestations, such as haemorrhage, hypotension, shock and acute renal failure. These snake venoms are able to activate the complement system and induce the generation of anaphylatoxins, whose mechanisms include the direct cleavage of complement components by snake venom metalloproteinases and serine proteinases present in the venoms. A metalloproteinase able to activate the three complement pathways and generate active anaphylatoxins, named C-SVMP, was purified from the venom of Bothrops pirajai. Considering the inflammatory nature of Bothrops venoms and the complement-activation property of C-SVMP, in the present work, we investigated the inflammatory effects of C-SVMP in a human whole blood model. The role of the complement system in the inflammatory process and its modulation by the use of compstatin were also investigated. C-SVMP was able to activate the complement system in the whole blood model, generating C3a/C3a desArg, C5a/C5a desArg and SC5b-9. This protein was able to promote an increase in the expression of CD11b, CD14, C3aR, C5aR1, TLR2 and TLR4 markers in leukocytes. Inhibition of component C3 by compstatin significantly reduced the production of anaphylatoxins and the Terminal Complement Complex (TCC) in blood plasma treated with the toxin, as well as the expression CD11b, C3aR and C5aR on leukocytes. C-SVMP was able to induce increased production of the cytokines IL-1β and IL-6 and the chemokines CXCL8/IL-8, CCL2/MCP-1 and CXCL9/MIG in the human whole blood model. The addition of compstatin to the reactions caused a significant reduction in the production of IL-1β, CXCL8/IL-8 and CCL2/MCP-1 in cells treated with C-SVMP. We therefore conclude that C-SVMP is able to activate the complement system, which leads to an increase in the inflammatory process. The data obtained with the use of compstatin indicate that complement inhibition may significantly control the inflammatory process initiated by Bothrops snake venom toxins.